Scrumbgc: um jogo de tabuleiro para apoiar o ensino de scrum - Moreira, Jose Augusto Oliveira da Costa (2024)
The teaching of Software Project Management to future professionals in the field is a topic frequently reported in the literature. Several studies have explored initiatives to measure the expectations of students and teachers regarding courses and classes, revealing cases of lessons that are overly theoretical and lack practical components, thus failing to allow students to perceive the real value and importance of knowledge involved in Software Project Management. Active Learning Methodologies have been applied and studied to provide Software Engineering (SE) students with a practical and proactive learning experience. Among these methodologies are the games, which can simulate simplified examples of real-life situations related to SE topics. Games are reported in the literature as teaching tools capable of increasing student motivation for learning. The goal of this Master’s Dissertation is to develop a board game to support the teaching of the Scrum framework, incorporating collaborative mechanics into its design. The game, named ScrumBGC, was developed based on a specific framework for designing board games to the Software Project Management field and underwent two Proofs of Concept with student groups from different educational institutions. The final evaluation was conducted using the IMMS instrument. Additionally, the MEEGA+ instrument was employed to assess the proposed game. The main findings indicate that ScrumBGC is a viable and effective option for teaching the Scrum framework. Data collected during the two proofs of concept carried out with undergraduate student groups from different institutions demonstrated the game’s acceptance and usefulness.